Analisis Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) Pada Gedung Pengadilan Negeri Kabanjahe - Ginting, Widya Septiani; Dalimunthe, Muhammad Erpandi (Power Elektronik : Jurnal Orang Elektro, 2025)
The increasing need for electrical energy in the government sector encourages the use of environmentally friendly alternative energy sources, one of which is the Solar Power Plant (PLTS). This study aims to analyze the potential, power requirements, and planning of the PLTS system that can be applied to the Kabanjahe District Court Building. The methods used include collecting data on existing electricity needs, analyzing local solar radiation potential, and simulating the system using PVsyst. The results of the analysis show that with an average daily energy consumption of 414 kWh and a total of 684 solar panels used, the implementation of this system also has the potential to reduce carbon emissions by ±14 tons of CO2 per year.